Integrated Nutrient Strategies for Enhancing Soil Health and Sustainable Phosphorus Management in Rice-Based Cropping Systems (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Sustaining productivity in intensive agroecosystems such as the rice-wheat system (9.2 mha in India) requires strategies that enhance nutrient use efficiency while preserving soil health. Phosphorus (P), the second most limiting nutrient after nitrogen, is particularly challenging due to its low bioavailability (
Keywords: integrated nutrient management; SDGs; phosphorus fractions; cropping system